2019
DOI: 10.1111/jfbc.13075
|View full text |Cite
|
Sign up to set email alerts
|

Saponin‐rich extracts fromHolothuria leucospilotamediate lifespan extension and stress resistance inCaenorhabditis elegansviadaf‐16

Abstract: Saponins are secondary metabolite compounds that can be found in sea cucumbers (Holothuroidea spp.). However, little is known about how saponin‐rich extracts from Holothuria leucospilota can delay and prolong the lifespan of the whole organism. In this study, anti‐aging effects of H. leucospilota extracts were studied on Caenorhabditis elegans. NMR analysis revealed that body wall n‐butanol‐extract of H. leucospilota (BW‐BU) is saponin‐rich. BW‐BU extracts exhibited antioxidant activities by 2,2ʹ‐diphenyl‐2‐pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…3.9.1 Water Extract Kitisin et al (2019) focused on the effect of sea cucumber extract on lifespan. In their research, a saponin-rich extract of Holothuria leucospilota increased the lifespan of C. elegans L4 and L1 at 5.92% and 15.76%, respectively, and significantly reduced the accumulation of lipofuscin, which is an ageing-biomarker.…”
Section: Ageing and Memory Impairmentsmentioning
confidence: 99%
“…3.9.1 Water Extract Kitisin et al (2019) focused on the effect of sea cucumber extract on lifespan. In their research, a saponin-rich extract of Holothuria leucospilota increased the lifespan of C. elegans L4 and L1 at 5.92% and 15.76%, respectively, and significantly reduced the accumulation of lipofuscin, which is an ageing-biomarker.…”
Section: Ageing and Memory Impairmentsmentioning
confidence: 99%
“…Hibiscus sabdariffa L. extract (HSE) and its main compound hydroxycitric acid increased the nuclear localization of DAF-16 and SKN-1, as well as protected against amyloid-β (Aβ)-induced toxicity, suggesting that the antiaging effect of HSE was dependent in a DAF-16 and SKN-1 (Koch, Weldle, Baier, Buchter, & Watjen, 2019). Meanwhile, echinacoside influenced longevity in C. elegans mainly by modulating the expression of daf-16 target genes, and a similar result was found in the body wall n-butanol extract of Holothuria leucospilota treatment (Kitisin, Suphamungmee, & Meemon, 2019;Wang et al, 2015). Astragalan, which targets DAF-16, prevented polyglutamine (polyQ) aggregation and alleviated polyQmediated neurotoxicity to prolong the adult lifespan of mutant worms exhibiting polyQ accumulation (Zhang et al, 2012).…”
Section: Daf-16mentioning
confidence: 69%
“…As shortened host longevity upon cryptococcal infections, several host fitnesses were interrupted. Our recent study showed that elevation of intracellular oxidative stress could accelerates aging process and induces the accumulation of lipofuscin in C. elegans [ 48 ]. Moreover, previous study demonstrated an increased expression of SOD-3 in E. faecalis infected C. elegans , which was dependently associated with DAF-16 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caenorhabditis elegans strains used in this study were Bristol N2 (wild-type), AU1 sek-1(ag1) , TJ1052 age-1(hx546) , CF1038 daf-16(mu86) , VC8 jnk-1(gk7) , VC199 sir-2.1(ok434) , AM1 osr-1(rm1) , TJ356 zIs356 [daf-16p::daf-16a/b::GFP + rol-6(su1006)] , CF1553 muIs84 [(pAD76) sod-3p::GFP + rol-6(su1006)] , and IG348 fasn-1(fr8);frIs7[nlp-29p::gfp, col-12p::DsRed] . All worms were age‐synchronized using hypochlorite treatment of gravid hermaphrodites (500 μl of 1 M NaOH, 600 μl of 1 M NaClO, and 3.9 ml of distilled water) as previously described [ 48 ]. The first stage (L1) larvae were transferred into fresh nematode growth medium (NGM) plates and fed on live‐ Escherichia coli strain OP50 at 20 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation